Review: The Coming Crisis. The Impact of Eschatology on Theology in Edwardian England - Morris, Jeremy (The journal of theological studies, 2003)
The Coming Crisis. The Impact of Eschatology on Theology in Edwardian England Mark D. Chapman 182 Sheffield (Journal for the Study of the New Testament, Supplement Series, 208.) Sheffield Academic Press 2001 £40/$64 1 84127 185 3